El don Juan, una inversión de la femineidad medieval demoniaca - Pizarro Granada, Maite (2022)
The amor hereos or aegritudo amoris was a type of medieval melancholy triggered by love rejection. It was caused by women but suffered by men, and it used to show a demonic kind of femininity. Many people would say this erotic conception disappeared, but there is enough evidence to believe don Juan’s tradition could be a different face of the same sort of love. According to this idea, the sinful behavior of don Juan would be a reproduction of the feminine eroticism exposed in the tradition of Spanish amatory treatises. Namely, it would have evolved from being a masculine melancholic disease to being a female one.